EKSPLORASI SEMANGAT BELAJAR SISWA - SISWI SMA PELITA KASIH DALAM MEMPELAJARI AKUNTANSI - Amat, Coroline Putri Tanjung; Sastrasasmita, Emillia (Jurnal Serina Abdimas, 2024)
The research conducted aims to explore students' motivation in learning accounting, which is a crucial aspect in understanding the factors influencing their academic achievement. The research methodology employed is qualitative, involving the use of questionnaires and students' opinions. The findings of the research indicate that internal factors such as intrinsic interest, conceptual understanding, and self-confidence significantly influence students' motivation. Additionally, environmental support, such as innovative and interactive teaching methods, as well as positive relationships with instructors, were also found to play a crucial role in enhancing learning motivation.The results of this research provide a deeper understanding of how to create a learning environment that motivates students and shapes their enthusiasm for developing interest and skills in accounting. The implications of these findings can be utilized by educators and policymakers to enhance the quality of accounting education at various levels.